Perang dunia pertama, deklarasi balfour dan kesannya terhadap Palestin (First world war, balfour declaration and their impacts on Palestine) - Ermy Azziaty Rozali; Azmul Fahimi Kamaruzaman (Institut Kajian Rantau Asia Barat, 2011)
The aftermath of First World War (1914-1918) left a tremendous impact on the Muslim world due to the defeat of the Ottoman Caliphate in the war. Consequently, this gave an opportunity for the British to control the Middle East region which led to the seizure of the Palestinian land by the immigrant Jews. This article discusses how the British after defeating the Ottoman Caliphate in 1917 went on to conquer Jerusalem. The promulgation of the Balfour Declaration by the British in the same year offered Palestine as ‘a national home’ for the Jew nation. Subsequently,the British were given a mandate by the League of Nations to rule Palestine, Iraq and Transjordan while France was given a mandate over Syria. Using historical analysis, this article evaluates how the British manipulated the mandate given to them to enable this to settle in western Palestine,namely between the Jordan River and the Mediterranean Sea. The rights to settle by the Jews was provided for in the Conference of San Remo. The analysis concludes that the formation of the state of Israel on 25th April, 12948, was directly influenced by the implementation of the British mandate in Palestine. This article also shows that the occupation of the Jews threatened the rights of the Palestinians. As a result of suppression and deprivation, the spirit of nationalism were raised among the Palestinians and the Arabs, with the Palestinians struggling to free their homeland from the Jews occupation